2017
DOI: 10.3892/ijo.2017.3928
|View full text |Cite
|
Sign up to set email alerts
|

miR-486 suppresses the development of osteosarcoma by regulating PKC-δ pathway

Abstract: Osteosarcoma is one of the most highly malignant types of cancer in adolescents and young adults with a high mortality rate. Despite advances in surgery, radiation therapy and chemotherapy, the prognosis for patients with osteosarcoma has not significantly improved over the past several decades. It is necessary to find new indicators of prognosis and therapeutic targets of osteosarcoma. Through the analysis of 40 osteosarcoma tissues, we found that the expression of miR-486 was low and the expression of PKC-δ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…For instance, miR-486-5p could act as an anti-oncogene and biomarker in non-small cell lung cancer (NSCLC), inhibiting the development and growth of NSCLC in mouse models 27, 28. The level of miR‑486 is low in osteosarcoma and patients who have low expression of miR-486 possess shorter median survival than those with higher miR‑486 29. Consistent with previous findings, it was discovered that miR-486-5p level was markedly reduced in breast cancer tissues than corresponding ANTs, thus miR-486-5p played as anti-oncogene in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, miR-486-5p could act as an anti-oncogene and biomarker in non-small cell lung cancer (NSCLC), inhibiting the development and growth of NSCLC in mouse models 27, 28. The level of miR‑486 is low in osteosarcoma and patients who have low expression of miR-486 possess shorter median survival than those with higher miR‑486 29. Consistent with previous findings, it was discovered that miR-486-5p level was markedly reduced in breast cancer tissues than corresponding ANTs, thus miR-486-5p played as anti-oncogene in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For osteosarcoma, another lncRNA-ATB promotes proliferation, migration, and invasion depending on the regulation of miR-200s [ 29 ]. In osteosarcoma tissue, miR-486 was down-regulated, and further found that miR-486 inhibited the targeting of PKC-δ signaling pathways, and ulteriorly inhibit the growth and invasion of osteosarcoma cells [ 30 ]. In prostate cancer tissue and cells, miR-486-5p sponged Snail, a key regulator of the epithelial-mesenchymal transition, to suppress cell migration and the invasive ability [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many studies revealed that miRNAs played vital roles in OS. For example, miR-486 suppressed proliferation and migration of OS [21]. And miR-504 facilitated growth and migration in OS [22].…”
Section: Introductionmentioning
confidence: 99%